Mock-epic poetry from Pope to Heine - Robertson, Ritchie (Oxford University Press, 2010)
This is a study of 18th- and early 19th-century poetry in English, French and German, focusing on the mock epic (from Pope's 'Dunciad' to Byron's 'Don Juan') as a critique of serious epic poetry and also as a literary means of exploring a wide range of sexual and religious issues in a humourous style.